A RAPID, SENSITIVE AND VALIDATED ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY AND TANDEM MASS SPECTROMETRY METHOD FOR DETERMINATION OF PAROMOMYCIN IN MICE PLASMA: APPLICATION TO PHARMACOKINETIC STUDY - Pinjari, M. Jakir S. K.; Somani, Rahul S.; Gilhotra, Ritu M. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: To develop and validate simple, sensitive, accurate and selective UPLC-MS/MS method for quantification of paromomycin (PARO) in mice plasma. Methods: Precipitation method was used for the extraction of plasma samples, an aliquot of 25 µl plasma samples was extracted using 10% perchloric acid in water. Chromatographic separation was performed using waters acquity ultra-performance liquid chromatography (UPLC) columns, BEH HILIC (50 mm× 2.1 mm, 1.7 µm) by a gradient mixture of acetonitrile and water (both containing 0.005% v/v trifluro acetic acid) as a mobile phase at the flow rate of 0.2 ml/min. The analyte was protonated in the positive electrospray ionization (ESI) interface and detected in multiple reactions monitoring (MRM) modes using the transition m/z 308.60-455.30. Results: The method had a short chromatographic run time of 3 min. Calibration curves were linear over wide ranges of 50.51-5019.22 ng/ml. The between and within-batch precision and accuracy of the method was determined by using 4 quality control samples, the highest % CV observed was 11.06. The mean recovery values are 78.17, 101.17 and 92.58 at low, medium and high-quality control levels; respectively. Conclusion: It was concluded that the developed and validated UPLC-MS/MS method was rapid, sensitive, accurate, precise, linear, and specific. Therefore, this method can be used for quantification of PARO in mice plasma with various advantages over the reported methods.